Upper limb peripheral neuropathy in sickle cell anemia: MR neurography appearances - Poh, Feng; Hlis, Rocco; Chhabra, Avneesh (Indian Journal of Radiology and Imaging, 2019)
Sickle cell anemia is an inherited disorder with many systemic complications. Peripheral neuropathy related to this disorder has been sparsely reported. We report an interesting case of upper limb peripheral neuropathy from sickle cell disease with emphasis on MR neurography appearances and electrophysiology correlation.
Keywords: Sickle cell anemia; peripheral neuropathy; MRI, MR neurography; MRN